A STUDY OF THE OIL CONTENT OF NIGERIAN GROWN MONODORA MYRISTICA SEEDS FOR ITS NUTRITIONAL AND INDUSTRIAL APPLICATIONS - Ajayi, I A; Adebowale, K O; Dawodu, F O; Oderinde, R A (Biological Sciences - PJSIR, 2004)
A study of the oil content of Monodora myristica for its potential and industrial applications has been undertaken. The study revealed that M. myristica seeds have high oil and protein content (21.79 ± 0.51% and 20.57 ± 0.38%, respec- tively). The carbohydrate content is quite high, (44.29 ± 1.50%) while it has low crude fibre content (4.70 ± 0.15%). The physico - chemical characteristics of the seed oil show that the oil has high acid value, (14.31 ± 0.32%); peroxide value, (15.90 ± 0.50%) and saponification value, (252.11 ± 2.50%). The iodine value of the seed oil which places the oil in the non-drying group is 85.00 ± 0.50%. Eight nutritionally valuable minerals of the seeds were determined and the result indicates the seeds to be richest in potassium 64.96 ± 1.60 ppm followed by magnesium (8.58 ± 1.50 ppm) and iron (8.40 ± 0.91 ppm). Fatty acid composition of the seed oil shows the oil to be rich in linoleic acid (35.52%) and oleic acid (33.15%). It also contains arachidic acid 9.52%. The other fatty acids present in the oil are palmitic acid, stearic acid, gadoleic acid and linoceric acid. Triacylglycerols (OOO, OPO / POO and OOL) accounted for over 57.70% of the total triacylglycerol content of the oil. In addition, high molecular weight triacylglycerols (containing fatty acid moiety > 18 carbons) was also detected in oil The potential domestic and industrial applicatioins of the oil under study are enumerated.